Atonement and human rights? : implications of the classic Reformed doctrine of atonement for the building of a human rights culture in contemporary Malawi - Thipa, Joseph Andrew (Stellenbosch : Stellenbosch University, 2009)
Thesis (DTh (Systematic Theology and Ecclesiology))-- Stellenbosch University, 2009.